Phenolic compounds from piper plants: A review on AI integration for extraction, quantification, antioxidant, antimicrobial properties, and food applications - Ida Madiha Yusoff; Siti Alyani Mat; Rosnani Hasham; Ismail Ware; Lashreena Ganesh (IDEAS, 2025)
Medicinal plants are rich in phenolic compounds, which are commonly found in food and nutraceutical products. The Piper plants contain a vast number of bioactive compounds, with phenolics being the most abundant and biologically necessary plant metabolites. The review assessed recent discussions on the various extraction techniques applied to extract phenolic compounds from Piper species. To enhance the extraction efficiency of Piper plants, innovative extraction methods are employed. Extraction methods such as microwave-assisted, ultrasonic-assisted, and enzyme-assisted extraction improve Piper extraction by utilizing low temperatures and reducing extraction durations. AI-driven optimization techniques are suggested to predict the optimal conditions. Reviewing the phenolic compounds extracted from Piper plants enhances a better understanding of the extraction process. Phenolic compounds found in Piper are renowned for their antioxidant and antimicrobial properties due to the presence of phenolic hydroxyl groups in ring structures. The antioxidant and antimicrobial properties of Piper also address the challenges in utilizing its phenolic compounds for biological purposes. The advanced AI-based analytical models are potential in the quantification of phenolic compounds by chromatographic and spectrophotometric methods. The Piper plants may become a promising source of phenolic compounds for use in the food industry upon diversification of extraction methods and quantification techniques.